Technology and Innovation in Adult Learning - King, Kathleen P. (Jossey Bass, 2017)
This book provides a compelling read, easily accessible siscussion, and abudant resources and straitegies for educators and learners interested in adult learning and technology.Many examples are provided to reflect on the possibilities of transforming one's own practice and also to apply those transformations across different areas of instruction, professional development, research, and knowledg-building agendas, goals, and projects.